Temperature and Frequency Dependence of Electric Field‐Induced Phase Transitions in PMN–0.32PT. Issue 7 (1st April 2014) - Wooldridge, Jenny; Stewart, Mark; Vecchini, Carlo; Cain, Markys G.; Gutmann, Matthias; Reece, Mike; Johnson, D.
<x xml:space="preserve">Abstract</x> Single crystal (1 − x)Pb(Mg1/3 Nb2/3)O3–xPbTiO3 [PMN–xPT] (x = 0.32) is a relaxor‐ferroelectric material known to exhibit 'giant' piezoelectric behavior, with achievable strains in excess of 1% for samples of certain particular crystallographic orientations and chemical compositions close to the morphotropic phase boundary. In this study, we investigate the electric field‐induced structural phase transitions in single crystal PMN–0.32PT with time‐of‐flight neutron diffraction and macroscopic electrical polarization measurements, and show that both the frequency of the applied ac field and the temperature of the sample are critical factors in determining these phase transition fields.